Hadith Practices in Ziarah Kubrā Tradition in Palembang Arabian Village - Dewi Fatonah (Jurnal Living Hadis, 2021)
Ziāra kubrā is of annual traditions practiced by the Arabs in Palembang to ‘greet’ the holy month Ramadan. It was initially practiced by the Arabs but then other part of the Palembang society join the rallies. It is a three days ceremony held in the last days of Sya’ban, the month just before Ramadan. Adopting Max Weber’s conception of social action, including its four types (traditional and affective action, instrumental rational and rational of values) this article shows that it is traditional action in that it preserves the tradition by the ulama. It is also affective in that it has a sort of emotional binding with the figures (ulamā and auliyā`, the clerics and the saints) and to the month of Sya’ban. It also has instrumental rationality for the people realize that they have all the capacities to run the tradition, in both terms of human resources and financial aspect. It also has rationality of values, for they are willing to get the berkah and benefits from the act of imitating the elders and preserving their tradition. All in all, this article argues that this tradition is of the practice of prophetic hadith on ziāra (pilgrimage) that are widely known from the hadith books.